Views of modern linguists in the interpretation of the “expressiveness” concept (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article deals with the interpretation of the “expressiveness” concept in modern linguistics. Scholars qualify speech expressions in different ways. It is quite clear that there is a distinction between speech expressiveness and accuracy, figurativeness, logic, etc. As for the interrelation of expression and expressiveness in linguistics, there is still a controversy, represented by four positions: the identification of expression and expressiveness; expression is a generic notion of expressiveness and other qualities of speech; expression derives from the category of expressiveness or it is a parallel concept to it. Often expression is identified with expressiveness, considering these concepts synonymous and explaining expression by means of expressiveness espcially in some studies in logic, psychology, linguistics. Thus, certain scholars in their linguistic researching define expression as expressive and figurative means of speech that distinguishes it from ordinary, stylistically neutral speech, making it bright, figurative, and emotionally coloured. Most linguists consider the concept of “expression” and “expressiveness” to be synonymous, confirming this idea with the fact of synonymous notions “expression” and “expressivenеss”, recorded by the “Great Defining Dictionary of Modern Ukrainian Language”.According to the second approach expression is represented as a generic concept of expressiveness and other speech qualities. In this case, the expression of the speech (statements, parts of the text or the whole text) is defined as a set of such characteristics (first of all accuracy, logic, clarity, expressiveness), which provide its full perception by the addressee (information understanding as close as possible). Speech qualities that determine speech expressiveness obtain different degrees of relevance (significance). Sometimes they are implemented by various expression means in functional speech styles. In terms of the third position expression is the derivative of the expressiveness concept that makes the language expressively coloured. Expressiveness is thus interpreted as a semantic category, which gives the expression due to the interaction in the content aspect of the language units, the text, the evaluative and emotional attitude of the speaker to the fact that happens in the internal or external world. Some linguists perceive expression as a separate linguistic category, which is a specific notion of expressiveness. The fourth approach can be outlined as follows: expression is a synonym of intensity and a parallel concept to expressiveness. It is understood as a kind of pragmatic information related to the concept of intensity (expressiveness). In general, this term delimitation process is very important and future-leading, as it contributes to their proper functioning in all branches of linguistics.
Keywords: expression; expressiveness; syntactic expressive means; utterances